ANALYZING THE DIFFERENCE OF e-BANKING SERVICES BETWEEN BANK CENTRAL ASIA AND BANK MANDIRI IN MANADO - Umboh, Yobel .; Worang, Frederik G.; Tumewu, Ferdinand J.; Tasik, Hizkia H.D (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: e-Banking is an electronic payment system that enables customers of a bank or other financial institutions to conduct a range of financial transactions through the financial institutions’ website. e-Banking has been widely used in developed and developing countries in the world. In Indonesia, the total users of e-Banking has increased since 2012 with 13.6 million of e-Banking users until 2016 with 50.3 million of e-Banking users. The aim of this study is to analyze the difference of e-Banking services between Bank Central Asia and Bank Mandiri in Manado. This research is a quantitative research and uses independent sample t-test. The sample size of this research is 100 customers of Bank Central Asia and Bank Mandiri in Manado. The results showed that e-Banking services based on Banking Mobile Application (Mobile Banking, Internet Banking, and SMS Banking) of Bank Central Asia and Bank Mandiri in Manado have a significant difference while the Automated Teller Machine (ATM) between Bank Central Asia and Bank Mandiri in Manado showed that there is no significant difference. The recommendation based on the results is Bank Mandiri have to more develop its e-Banking system application to maintain and create more customer delight.Keyword: e-banking, banking mobile application, mobile banking, internet banking, sms banking, automated teller machine.